Antisickling and Antibacterial Activities of Anthocleista schweinfurthii Gilg. (Gentianaceae) from Non-human Primates Pharmacopoeia in Democratic Republic of the Congo - Ngunde-te-Ngunde, Samy; Lengbiye, Emmanuel Moke; Joseph, Tshidibi Dipa; Franck, Kengo Velantia; Djolu, Ruphin D.; Mesango, Colette Ashande; Gbolo, Benjamin Z.; Jeff, Iteku Bekomo; Mpiana, Pius Tshimankinda; Ngbolua, Koto-te-Nyiwa (Budapest International Research and Critics University, 2019)
The aim of the present study was to evaluate the Chemical composition and bioactivity of Anthocleista schweinfurthii Gilg (Gentianaceae) fruits, leaves, root bark and stem bark extracts against Sickle cell disease (SCD) and associated bacteria. The antisickling and antibacterial activities were carried out using Emmel and micro-dilution methods respectively. The results revealed that the fruits, leaves, root bark and stem bark extracts of A. schweinfurthii contains various secondary metabolites such as the alkaloids, saponins, total polyphenols, flavonoids, tannins, anthocyanis, leuco-anthocyanins and quinones. The ethyl acetate and methanol extracts displayed antisickling activity. While, the antibacterial activity of different plant extracts tested was weak toward tested bacterial strains (CMI ≥125μg/mL). The antibacterial activity can be improved by bio-guided fractionation of the n-hexane, ethyl acetate or methanol soluble fraction. This study provides for the first time a scientific basis for the in vitro antisickling activity of A. schweinfurthii.